The Psychological Factors Worsening Speaking Skill in English Language - Ruzigul Rajapova (International Journal on Integrated Education, 2022)
This article gives information about some psychological factors like low self-confidence, lack of motivation, hesitation, shyness and fear of mistakes that have negative impact on improving speaking ability in English language. It describes how they are derived. It states that so many problems result from some kinds of psychological factors that English language learners may come across while speaking.